The Effectiveness of Betel Leaf (Piper betle) Extract on the Growth of Staphylococcus epidermidis - Pauzan, Pauzan; Mentari, Ika Nurfajri; Kurniawan, Ari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Staphylococcus epidermidis, a gram-positive bacterium typically found on the skin, can cause infections, particularly in individuals with implanted medical devices. Due to its ability to resist standard antibiotics and create biofilms, finding new antibacterial solutions is crucial. Betel leaves (Piper betle) are recognized for containing active components like flavonoids, saponins, polyphenols, and essential oils, suggesting they could act as natural antibacterial agents. This research sought to assess how well green betel leaf extract inhibits S. epidermidis growth in a controlled laboratory setting. The research involved a laboratory-based experiment utilizing a completely randomized design. The disc diffusion method on Nutrient Agar media was employed to test three extract concentrations (40, 60, and 80 mg/disk), using erythromycin as a positive control and DMSO as a negative control. Each treatment was repeated four times. The diameter of the inhibition zones was measured following a 24-hour incubation period at 37°C. The Shapiro–Wilk normality test, one-way ANOVA, and Tukey HSD test were used to analyze the data collected. The findings revealed that the concentrations of 60 and 80 mg/disk exhibited substantial antibacterial effects, producing an average inhibition zone of 14.25 mm, which was significantly different from the negative control (p < 0.05). In conclusion, green betel leaf extract is effective at suppressing the growth of S. epidermidis and shows promise as a source for developing a natural antibacterial treatment.